STRATEGI DALAM MENINGKATKAN PERTUMBUHAN DEBITU SMALL MEDIUM ENTERPRISE BANK CIMB NIAGA CABANG MEDAN BUKIT BARISAN - Afrizal .; Iskandarini .; Sutarman . (Universitas Islam Negeri Sumatera Utara Medan, 2015)
The strategy set by Bank CIMB Niaga in promoting growth Debtor Small MediumEnterprise Branch Medan Bukit Barisan up to date has focused on the application ofexcellent service to attract customers and prospective debtor as a partner in apartnership. However it is felt not to be able to make the maximum contribution inincreasing the number of Debtors Branch Medan Bukit Barisan so diada-kan need aresearch study to find additional strategies in doubt-sanaannya signifikant able to giveeffect to this increase SME Debtor Bank CIMB Niaga. In the Division of Small MediumEnterprise [SME] Bank CIMB Niaga Medan Bukit Barisan, loan products as one of themajor and mainstay products decreased Debtor growth in 2010 and 2011.Keywords: Strategi, Debitu Small Medium Enterprise, Bank Cimb Niaga.